Optical glass and optical element
By optimizing the composition of optical glass with controlled oxide contents and ratios, the high refractive index and low dispersion are maintained, addressing the cost issue of Gd2O3 and Ta2O5, suitable for optical elements.
Patent Information
- Application Number
- JP2024093464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-21
- Filing Date
- 2024-06-10
- Publication Date
- 2025-01-09
AI Technical Summary
The high cost of Gd2O3 and Ta2O5 components in optical glass compositions with high refractive index has led to a need for reducing their total content while maintaining or enhancing the refractive index.
A glass composition with controlled contents of SiO2, B2O3, La2O3, Y2O3, TiO2, ZrO2, Nb2O5, and other oxides, limiting Gd2O3 and Ta2O5 to specific ranges, along with optimized molar ratios, to achieve a high refractive index without excessive costs.
The solution provides an optical glass with a low total content of Gd2O3 and Ta2O5, maintaining a high refractive index and low dispersion, suitable for optical elements, while reducing production costs.
Smart Images

Figure 2025003357000001 
Figure 2025003357000002 
Figure 2025003357000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass and an optical element. [Background technology]
[0002] In recent years, optical glasses with high refractive indices have been proposed as materials for optical elements (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2013 / 146378 Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 (WO2013 / 146378) discloses a glass composition with a high total content of Gd2O3 and Ta2O5 as a glass composition that achieves a high refractive index (see the examples in WO2013 / 146378). However, since Gd2O3 and Ta2O5 are expensive components whose unit prices have risen sharply in recent years, in order to reduce the cost of glass, a glass with a low total content of Gd2O3 and Ta2O5 is desirable.
[0005] In view of the above, an object of one aspect of the present invention is to provide an optical glass having a low total content of Gd2O3 and Ta2O5 and a high refractive index. [Means for solving the problem]
[0006] One aspect of the present invention is as follows. [1] In the glass composition based on oxides expressed in mole percent, SiO2 content is 1.00% or more and 30.00% or less, B2O3 content is 1.00% or more and 40.00% or less, La2O3 content is 5.00% or more and 40.00% or less, Gd2O3 content is 0.00% or more and 3.50% or less, Y2O3 content is 0.50% or more and 20.00% or less, TiO2 content is 5.00% or more and 30.00% or less, ZrO2 content is 0.00% or more and 20.00% or less, Nb2O5 content is 0.00% or more and 20.00% or less, The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more and 3.50% or less, The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more; The total content of TiO2, ZrO2 and Nb2O5 (TiO2+ZrO2+Nb2O5) is 23.00% or more and 36.00% or less, The total content of alkaline earth metal oxides RO and alkali metal oxides RO (RO+RO) is 3.50% or more, The molar ratio of the Gd2O3 content to the SiO2 content (Gd2O3 / SiO2) is 0.00 or more and 0.23 or less; The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 0.80 or more and 1.56 or less; The molar ratio of the SiO2 content to the La2O3 content (SiO2 / La2O3) is 0.87 or less; The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.15 or more and 0.34 or less, and The molar ratio of TiO2 content to B2O3 content (TiO2 / B2O3) is 0.70 or more and 1.10 or less; Optical glass. [2] The optical glass according to [1], having an Al2O3 content of 0.00% or more and 2.00% or less. [3] The optical glass according to [1] or [2], having an Nb2O5 content of 0.10% or more and 20.00% or less. [4] The optical glass according to any one of [1] to [3], having a WO3 content of 0.00% or more and 0.40% or less. [5] The optical glass according to any one of [1] to [4], wherein the total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less. [6] The optical glass according to any one of [1] to [5], in which the combined content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more and 10.50% or less. [7] The optical glass according to any one of [1] to [6], wherein the molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.17 or more and 0.34 or less. [8] The optical glass according to any one of [1] to [7], wherein the molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 1.20 or more and 1.56 or less. [9] The optical glass according to any one of [1] to [8], wherein the molar ratio of the SiO2 content to the La2O3 content (SiO2 / La2O3) is 0.50 or more and 0.87 or less.
[10] The optical glass according to any one of [1] to [9], wherein the combined content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more and 2.50% or less.
[11] The Al2O3 content is equal to or greater than 0.00% and equal to or less than 2.00%; The Nb2O5 content is 0.10% or more and 20.00% or less, The WO3 content is 0.00% or more and 0.40% or less, The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less; The total content (RO+RO) of alkaline earth metal oxide RO and alkali metal oxide RO is 3.50% or more and 10.50% or less, The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.17 or more and 0.34 or less; The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 1.20 or more and 1.56 or less, The molar ratio of the SiO2 content to the La2O3 content (SiO2 / La2O3) is 0.50 or more and 0.87 or less, and The optical glass according to any one of [1] to
[10] , wherein the total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more and 2.50% or less.
[12] An optical element comprising the optical glass according to any one of [1] to
[11] . Effect of the Invention
[0007] According to one aspect of the present invention, it is possible to provide an optical glass having a low total content of Gd2O3 and Ta2O5 and a high refractive index, and an optical element made of this optical glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Optical glass] In the present invention and this specification, the glass composition of optical glass is expressed as a glass composition based on oxides expressed in mole percent. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides that exist in the glass after being completely decomposed during melting. In the glass composition expressed in mole percent, the glass composition is expressed on a molar basis (mol%, molar ratio). Hereinafter, for glass compositions expressed in mole percent, "mol%" will also be simply referred to as "%".
[0009] In the present invention and this specification, the content of a component being 0%, 0.0% or 0.00%, or not containing or not introducing, means that the component is substantially not contained, and the content of the component is at or below the impurity level. At or below the impurity level means, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%". The content of a certain component being "0% or more", "0.0% or more", or "0.00% or more" means that the component is an optional component.
[0010] The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed for each element using ICP-AES. The analytical values are then converted into oxide notation. The analytical values obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values converted from the analytical values may also contain an error of about ±5%.
[0011] In the present invention and this specification, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).
[0012] In the present invention and this specification, the Abbe number νd is used as a value representing a property related to dispersion, and is expressed by the following formula. νd=(nd-1) / (nF-nC) In the above formula, nF is the refractive index at the F line of blue hydrogen (wavelength 486.13 nm), and nC is the refractive index at the C line of red hydrogen (656.27 nm).
[0013] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.
[0014] <Glass composition> SiO2 is a glass network component, and as its content increases, the viscosity of the glass increases, but the melting property tends to decrease. From the above viewpoints, the SiO2 content is 1.00% or more and 30.00% or less. The SiO2 content is preferably 2.00% or more, and more preferably in this order: 3.00% or more, 4.00% or more, 5.00% or more, 6.00% or more, 7.00% or more, 8.00% or more, 9.00% or more, 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 13.50% or more, 14.00% or more, and 14.50% or more. In addition, the SiO2 content is preferably 29.00% or less, and more preferably in this order: 28.00% or less, 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.00% or less, 22.00% or less, 21.00% or less, 20.00% or less, 19.00% or less, 18.00% or less, 17.50% or less, 17.00% or less, and 16.50% or less.
[0015] B2O3 is a glass network component and contributes to improving meltability. From the above viewpoints, the B2O3 content is 1.00% or more, preferably 2.00% or more, more preferably 3.00% or more, 4.00% or more, 5.00% or more, 6.00% or more, 7.00% or more, 8.00% or more, 9.00% or more, 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, 17.00% or more, 17.50% or more, 18.00% or more, 18.50% or more, 19.00% or more, and 19.50% or more in that order. On the other hand, the effect of volatilization increases as the content of B2O3 increases. Therefore, from the viewpoint of ease of controlling optical properties, the B2O3 content is 40.00% or less, preferably 39.00% or less, more preferably 38.00% or less, 37.00% or less, 36.00% or less, 35.00% or less, 34.00% or less, 33.00% or less, 32.00% or less, 31.00% or less, 30.00% or less, 29.00% or less, 28.00% or less, 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.50% or less, 23.00% or less, and 22.50% or less in that order.
[0016] Regarding the molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2), when the value of this molar ratio is small, the glass tends to become highly dispersed, and when the value of this molar ratio is large, the refractive index of the glass tends to decrease. From the above viewpoints, the molar ratio (B2O3 / SiO2) is 0.80 or more and 1.56 or less. The molar ratio (B2O3 / SiO2) is preferably 0.85 or more, and more preferably 0.90 or more, 0.95 or more, 1.00 or more, 1.05 or more, 1.10 or more, 1.15 or more, 1.20 or more, 1.21 or more, 1.22 or more, and 1.23 or more in that order. Further, the molar ratio (B2O3 / SiO2) is preferably 1.55 or less, and more preferably 1.54 or less, 1.53 or less, 1.52 or less, 1.51 or less, 1.50 or less, 1.49 or less, and 1.48 or less, in that order.
[0017] The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. Gd2O3 and Ta2O5 are components that increase the refractive index of glass, but from the viewpoint of reducing the cost of glass, the smaller the total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) the more preferable. The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) of the above glass is 3.50% or less, preferably 3.00% or less, more preferably 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, and most preferably 0.00%. The respective contents of Gd2O3 and Ta2O5 will be described later.
[0018] La2O3 is a component that contributes to a high refractive index and low dispersion of glass. When the La2O3 content is low, the refractive index tends to decrease, and when the La2O3 content is high, the glass tends to crystallize easily. From the above viewpoints, the La2O3 content is 5.00% or more and 40.00% or less. The La2O3 content is preferably 6.00% or more, and more preferably in this order: 7.00% or more, 8.00% or more, 9.00% or more, 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, 17.00% or more, 18.00% or more, 19.00% or more, 20.00% or more, 20.50% or more, 21.00% or more, 21.50% or more, 22.00% or more, and 22.50% or more. Furthermore, the La2O3 content is preferably 39.00% or less, and more preferably in this order: 38.00% or less, 37.00% or less, 36.00% or less, 35.00% or less, 34.00% or less, 33.00% or less, 32.00% or less, 31.00% or less, 30.00% or less, 29.00% or less, 28.00% or less, 27.50% or less, 27.00% or less, 26.50% or less, 26.00% or less, 25.50% or less, 25.00% or less, 24.50% or less, 24.00% or less, and 23.50% or less.
[0019] The Gd2O3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. Gd2O3 is a component that contributes to a high refractive index and low dispersion of glass. However, Gd2O3 is a component with a high unit price, increases the specific gravity, makes glass easier to crystallize, and is also a component that reduces the melting property of glass. Therefore, when Gd2O3 is contained in glass, it is preferable to contain it in as small an amount as possible. From the above viewpoint, the Gd2O3 content is 3.50% or less, and more preferably 3.00% or less, 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less in that order, and is most preferably 0.00%.
[0020] Y2O3 is a component that contributes to increasing the refractive index and decreasing the dispersion of glass. However, if the Y2O3 content is high, the glass tends to crystallize easily. From the above viewpoints, the Y2O3 content is 0.50% or more and 20.00% or less. The Y2O3 content is preferably 1.00% or more, and more preferably 2.00% or more, 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, and 5.00% or more in that order. Furthermore, the Y2O3 content is preferably 19.00% or less, and more preferably in this order: 18.00% or less, 17.00% or less, 16.00% or less, 15.00% or less, 14.00% or less, 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.00% or less, 6.50% or less, 6.00% or less, and 5.50% or less.
[0021] From the viewpoint of increasing the refractive index of the glass, the total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more, preferably 27.00% or more, and more preferably 27.50% or more, 27.60% or more, 27.70% or more, 27.80% or more, 27.90% or more, and 28.00% or more in that order. From the viewpoint of suppressing crystallization of the glass, the total content (La2O3 + Gd2O3 + Y2O3) is preferably 40.00% or less, and more preferably 35.00% or less, 34.00% or less, 33.00% or less, 32.50% or less, 32.00% or less, 31.50% or less, 31.00% or less, 30.50% or less, 30.00% or less, 29.50% or less, and 29.00% or less, in that order.
[0022] The molar ratio of the Gd2O3 content to the SiO2 content (Gd2O3 / SiO2) is 0.00 or more, and can be 0.00, 0.00 or more, or more than 0.00. From the viewpoint of reducing the specific gravity of the glass, the molar ratio (Gd2O3 / SiO2) is 0.23 or less, preferably 0.22 or less, more preferably 0.21 or less, 0.20 or less, 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, and 0.01 or less in that order, and is most preferably 0.00.
[0023] From the viewpoint of increasing the refractive index of the glass, the molar ratio of the SiO2 content to the La2O3 content (SiO2 / La2O3) is 0.87 or less, preferably 0.85 or less, and more preferably 0.80 or less, 0.79 or less, 0.78 or less, 0.76 or less, 0.75 or less, 0.74 or less, 0.73 or less, 0.72 or less, and 0.71 or less, in that order. The molar ratio (SiO2 / La2O3) can be greater than 0.00, and from the viewpoint of maintaining glass stability, is preferably 0.05 or more, and more preferably 0.10 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, 0.35 or more, 0.40 or more, 0.45 or more, 0.50 or more, 0.55 or more, and 0.60 or more, in that order.
[0024] Regarding the molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3), as the value of this molar ratio decreases, the refractive index of the glass tends to decrease, and as the value of this molar ratio increases, the glass tends to crystallize more easily. From the above viewpoints, the molar ratio (Y2O3 / B2O3) is 0.15 or more and 0.34 or less. The molar ratio (Y2O3 / B2O3) is preferably 0.16 or more, and more preferably 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, and 0.23 or more in that order. Further, the molar ratio (Y2O3 / B2O3) is preferably 0.33 or less, and more preferably 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, and 0.28 or less, in that order.
[0025] TiO2 is a component that increases the refractive index of glass. However, TiO2 is a component that decreases the transmittance of glass, and glass tends to crystallize more easily when its content is high. From the above viewpoints, the TiO2 content is 5.00% or more and 30.00% or less. The TiO2 content is preferably 6.00% or more, and more preferably in this order: 7.00% or more, 8.00% or more, 9.00% or more, 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 15.50% or more, 16.00% or more, 16.50% or more, and 17.00% or more. Further, the TiO2 content is preferably 29.00% or less, and more preferably 28.00% or less, 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.00% or less, 22.50% or less, 22.00% or less, 21.50% or less, 21.00% or less, and 20.50% or less, in that order.
[0026] The ZrO2 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. ZrO2 is a component that contributes to a high refractive index and low dispersion of glass. However, ZrO2 is a component that increases the viscosity of glass, and the glass tends to become more easily devitrified when its content increases. From the above viewpoints, the ZrO2 content is 20.00% or less, preferably 19.00% or less, and more preferably 18.00% or less, 17.00% or less, 16.00% or less, 15.00% or less, 14.00% or less, 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, and 7.50% or less in that order. Further, the ZrO2 content is preferably 1.00% or more, and more preferably in the order of 2.00% or more, 2.50% or more, 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, 5.00% or more, 5.50% or more, 6.00% or more, and 6.50% or more.
[0027] The Nb2O5 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. Nb2O5 is a component that contributes to increasing the refractive index and decreasing the dispersion of the glass. From the viewpoint of controlling the dispersibility of the glass, the Nb2O5 content is 20.00% or less, preferably 19.00% or less, and more preferably 18.00% or less, 17.00% or less, 16.00% or less, 15.00% or less, 14.00% or less, 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, 9.00% or less, 8.00% or less, 7.00% or less, 6.50% or less, 6.00% or less, 5.50% or less, 5.00% or less, and 4.50% or less in that order. The Nb2O5 content is preferably 0.10% or more, more preferably 0.50% or more, 1.00% or more, and further preferably 1.50% or more.
[0028] From the viewpoint of suppressing crystallization and suppressing high dispersion of the glass, the total content of TiO2, ZrO2 and Nb2O5 (TiO2 + ZrO2 + Nb2O5) is 36.00% or less, preferably 34.00% or less, and more preferably 33.50% or less, 33.00% or less, 32.50% or less, 32.00% or less, 31.50% or less, 31.00% or less, 30.50% or less, 30.00% or less, and 29.50% or less, in that order. From the viewpoint of increasing the refractive index of the glass, the total content (TiO2 + ZrO2 + Nb2O5) is 23.00% or more, preferably 24.00% or more, and more preferably 24.50% or more, 25.00% or more, 25.50% or more, 26.00% or more, 26.50% or more, 27.00% or more, 27.50% or more, 28.00% or more, and 28.50% or more in that order.
[0029] Regarding the molar ratio of TiO2 content to B2O3 content (TiO2 / B2O3), as the value of this molar ratio increases, the glass tends to become highly dispersed, while as the value of this molar ratio decreases, the refractive index of the glass tends to decrease. From the above viewpoints, the molar ratio (TiO2 / B2O3) is 0.70 or more and 1.10 or less. The molar ratio (TiO2 / B2O3) is preferably 0.72 or more, more preferably 0.74 or more, 0.75 or more, and further preferably 0.76 or more. Further, the molar ratio (TiO2 / B2O3) is preferably 1.09 or less, and more preferably 1.08 or less, 1.07 or less, 1.06 or less, 1.05 or less, 1.04 or less, and 1.03 or less in that order.
[0030] When alkaline earth metal oxide is represented as RO and alkali metal oxide is represented as R2O, the total content of the alkaline earth metal oxide RO and the alkali metal oxide RO (RO+R2O) is 3.50% or more, and preferably 3.60% or more, from the viewpoint of reducing the viscosity of the glass, and is more preferably 3.70% or more, 3.80% or more, 3.90% or more, 4.00% or more, 4.10% or more, 4.20% or more, 4.30% or more, 4.40% or more, 4.50% or more, 4.60% or more, 4.70% or more, 4.80% or more, 4.90% or more, 5.00% or more, 5.10% or more, 5.20% or more, 5.30% or more, 5.40% or more, 5.50% or more, 5.60% or more, and 5.70% or more in that order. On the other hand, from the viewpoint of suppressing crystallization of the glass, the total content (RO+R2O) is preferably 12.00% or less, and more preferably 11.50% or less, 11.00% or less, 10.50% or less, 10.00% or less, 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.40% or less, 7.30% or less, 7.20% or less, and 7.10% or less, in that order.
[0031] Regarding the content of each component of the alkali metal oxide R2O, the Li2O content is 0.00% or more and can be 0.00% or more. From the viewpoints of further improving the thermal stability of the glass, suppressing a decrease in the glass transition temperature (thereby improving machinability), and improving chemical durability and weather resistance, the Li2O content is preferably 5.00% or less, and more preferably 4.00% or less, 3.00% or less, and 2.00% or less in that order. The respective contents of Na2O, K2O, Rb2O and Cs2O are 0.00% or more, and can be 0.00% or more than 0.00%. Na2O, K2O, Rb2O and Cs2O all have the function of improving the meltability of glass, but as their contents increase, the thermal stability, chemical durability, weather resistance and machinability of glass tend to decrease. Therefore, the respective contents of Na2O, K2O, Rb2O and Cs2O are preferably 5.00% or less, more preferably 4.00% or less, 3.00% or less and 2.00% or less in that order. Rb2O and Cs2O are expensive components, and compared with Li2O, Na2O, and K2O, are components that are not suitable for general-purpose glass. From the viewpoints of improving the meltability of glass, lowering the glass transition temperature Tg, and lowering the specific gravity of glass while maintaining the thermal stability, chemical durability, weather resistance, and machinability of glass, it is preferable that the alkali metal oxide R2O contained in the above glass is one or more selected from the group consisting of Li2O, Na2O, and K2O.
[0032] The alkaline earth metal oxide RO contained in the glass is preferably one or more selected from the group consisting of MgO, CaO, SrO and BaO. The content of each of MgO, CaO, SrO and BaO is 0.00% or more, and may be 0.00% or more than 0.00%. From the viewpoint of suppressing devitrification of the glass and realizing desired optical properties, the content of each of MgO, CaO, SrO and BaO is preferably 8.00% or less, more preferably 7.00% or less, and further preferably 6.00% or less, 5.00% or less, 4.00% or less, 3.00% or less, and 2.00% or less, in that order.
[0033] Ta2O5 is an expensive component. From the viewpoint of reducing the cost of the glass, the Ta2O5 content is preferably 2.50% or less, more preferably 2.00% or less, 1.50% or less, 1.00% or less, and 0.50% or less in that order, and is most preferably 0.00%.
[0034] The Al2O3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. From the viewpoint of suppressing crystallization of glass, the Al2O3 content is preferably 2.00% or less, more preferably 1.50% or less, 1.00% or less, and 0.50% or less in that order, and is most preferably 0.00%.
[0035] The WO3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. WO3 is a component that contributes to increasing the refractive index and decreasing the dispersion of glass, but when the content is high, the transmittance of glass tends to decrease. From the viewpoint of suppressing the decrease in the transmittance of glass, the WO3 content is preferably 0.40% or less, more preferably 0.30% or less, 0.20% or less, and 0.10% or less in that order, and most preferably 0.00%.
[0036] The Bi2O3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. Bi2O3 is a component that contributes to increasing the refractive index and decreasing the dispersion of glass, but as the content increases, the transmittance of the glass tends to decrease. From the viewpoint of suppressing the decrease in the transmittance of the glass, the Bi2O3 content is preferably 0.40% or less, more preferably 0.30% or less, 0.20% or less, and 0.10% or less, in that order, and most preferably 0.00%.
[0037] The ZnO content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. ZnO is a component that lowers the melting temperature of glass and also a component that lowers the glass transition temperature Tg. The ZnO content is preferably 0.10% or more, more preferably 0.50% or more, 0.70% or more, 0.90% or more, and 1.00% or more in that order. On the other hand, from the viewpoint of suppressing crystallization of the glass, the ZnO content is preferably 12.00% or less, and more preferably 11.00% or less, 10.00% or less, 9.00% or less, and 8.00% or less in that order.
[0038] As for other glass components, taking into consideration the environmental impact, the As2O3 content is preferably 0.10% or less, more preferably 0.01% or less, and most preferably 0.00%. Also, taking into consideration the environmental impact, the PbO content is preferably 1.00% or less, more preferably 0.50% or less, and more preferably 0.10% or less, and most preferably 0.00%.
[0039] Sb2O3 is a component that can be added as a clarifier. Although a small amount of Sb2O3 can suppress the decrease in light transmittance caused by the inclusion of impurities such as Fe, the coloring of the glass tends to increase when the amount of Sb2O3 added is increased. Therefore, the amount of Sb2O3 added is preferably 0.00% or more and 0.10% or less, more preferably 0.00% or more and 0.08% or less, and even more preferably 0.00% or more and 0.05% or less, in terms of the total amount of Sb2O3 added. The Sb2O3 content by the total amount means the Sb2O3 content by mass % when the total amount of glass components other than Sb2O3 is taken as 100 mass %.
[0040] SnO2 can also be added as a clarifier, but if it is added in an amount exceeding 1.00% by weight, the glass will become colored, and when the glass is heated and softened and reshaped by press molding or the like, Sn will become the starting point for crystal nucleation, causing a tendency for devitrification. Therefore, the amount of SnO2 added is preferably 0.00% or more and 1.00% or less by weight, more preferably 0.00% or more and 0.50% or less, and it is particularly preferable to not add any SnO2. The SnO2 content by weight refers to the SnO2 content expressed in mass% when the total content of glass components other than SnO2 is taken as 100 mass%.
[0041] <Glass properties> (Refractive index nd) The glass can be a high refractive index glass by having the above glass composition. From the viewpoint of usefulness as a material for optical elements, the refractive index nd of the glass is preferably 1.9430 or more, more preferably 1.9450 or more, 1.9500 or more, and further preferably 1.9520 or more, in that order. From the viewpoint of usefulness as a material for optical elements, the refractive index nd of the above glass is preferably 1.9800 or less, and more preferably 1.9790 or less, 1.9780 or less, 1.9770 or less, 1.9760 or less, 1.9750 or less, 1.9740 or less, 1.9730 or less, 1.9720 or less, 1.9710 or less, 1.9700 or less, 1.9690 or less, 1.9680 or less, 1.9670 or less, 1.9660 or less, 1.9650 or less, 1.9640 or less, 1.9630 or less, 1.9620 or less, 1.9610 or less, 1.9600 or less, 1.9590 or less, 1.9580 or less, 1.9570 or less, 1.9560 or less, and 1.9550 or less, in that order.
[0042] (Abbe number νd) The above glass has the above glass composition and thus can exhibit low dispersion. From the standpoint of usefulness as a material for optical elements, the Abbe number vd of the above glass is preferably 30.00 or greater, more preferably 30.20 or greater, 30.50 or greater, 31.00 or greater, 31.50 or greater, 32.00 or greater, or 32.10 or greater. From the viewpoint of usefulness as a material for optical elements, the Abbe number vd of the above glass is preferably 34.00 or less, and more preferably 33.50 or less, 33.00 or less, and 32.50 or less, in that order.
[0043] (specific gravity) The refractive power of the optical elements that make up an optical system is determined by the refractive index of the glass that makes up the optical element and the curvature of the optical functional surface of the optical element (the surface through which the light rays to be controlled enter and exit). If you try to increase the curvature of the optical functional surface, the thickness of the optical element also increases. As a result, the optical element becomes heavier. In contrast, if glass with a high refractive index is used, it is possible to obtain a large refractive power without increasing the curvature of the optical functional surface. From the above, if the refractive index can be increased while suppressing an increase in the specific gravity of the glass, it will be possible to reduce the weight of an optical element having a certain refractive power. From the above viewpoints, the specific gravity of the glass is preferably 5.50 or less, and more preferably 5.20 or less, 5.19 or less, 5.18 or less, 5.17 or less, 5.16 or less, 5.15 or less, 5.10 or less, 5.05 or less, and 5.00 or less in that order. Since a lower specific gravity is preferable from the viewpoint of reducing the weight of the optical element, the lower limit of the specific gravity of the glass is not particularly limited. In one embodiment, the specific gravity of the glass can be, for example, 4.80 or more, 4.85 or more, 4.90 or more, 4.92 or more, 4.93 or more, 4.94 or more, or 4.95 or more. In the present invention and this specification, the "specific gravity" is a value measured by Archimedes' method.
[0044] (Coloring degree λ5, λ 70 ) The light transmittance of the glass, specifically, the suppression of the shift of the light absorption edge on the short wavelength side to longer wavelengths, is the coloring degree λ5 and λ 70 The coloring degree λ5 represents the wavelength at which the spectral transmittance (including surface reflection loss) of a glass with a thickness of 10±0.1 mm is 5% from the ultraviolet region to the visible region. λ 70 represents the wavelength at which the spectral transmittance measured by the method described for λ5 is 70%. 70 is a value measured in the wavelength range of 250 to 700 nm. The spectral transmittance T (%) of glass in the present invention and this specification is calculated by dividing the intensity of light incident perpendicularly on one of two optically polished parallel planes of a glass sample by the intensity of light I in The intensity of the light that passes through the glass sample and exits from the other side is I out When T(%)=I out / I in ×100 It is expressed as: Coloring degree λ5 and λ 70According to the method, the absorption edge on the short wavelength side of the spectral transmittance can be quantitatively evaluated. For example, when lenses are bonded together with an ultraviolet-curable adhesive to produce a cemented lens, the adhesive is cured by irradiating it with ultraviolet light through an optical element. From the viewpoint of efficiently curing the ultraviolet-curable adhesive, it is preferable that the absorption edge on the short wavelength side of the spectral transmittance is in a short wavelength range. As an index for quantitatively evaluating the absorption edge on the short wavelength side, the coloring degree λ5 and λ 70 One or more of the following may be used. The λ5 of the above glass can preferably exhibit a λ5 of 370 nm or less. The λ5 is more preferably 369 nm or less, and even more preferably 368 nm or less. The shorter the wavelength of λ5, the more preferable it is, and the lower limit is not particularly limited. In one embodiment, the λ5 can be 340 nm or more, 341 nm or more, 342 nm or more, 343 nm or more, 344 nm or more, 345 nm or more, 346 nm or more, or 347 nm or more. The glass preferably has a λ of 440 nm or less. 70 It can be shown that λ 70 is more preferably 439 nm or less, 438 nm or less, 437 nm or less, 436 nm or less, 435 nm or less, 434 nm or less, 433 nm or less, 432 nm or less, 431 nm or less, 430 nm or less, 429 nm or less, 428 nm or less, and 427 nm or less, in that order. 70 is more preferable as the wavelength is shorter, and the lower limit is not particularly limited. 70 can be 390 nm or greater, 391 nm or greater, 392 nm or greater, 393 nm or greater, or 394 nm or greater.
[0045] (glass transition temperature Tg) From the viewpoint of machinability (more specifically, from the viewpoint of resistance to breakage when mechanically processing the glass such as cutting, milling, grinding, polishing, etc.), the glass transition temperature Tg of the above-mentioned glass is preferably 680°C or higher, and more preferably 685°C or higher, 686°C or higher, 687°C or higher, 688°C or higher, 690°C or higher, 691°C or higher, 692°C or higher, 693°C or higher, 694°C or higher, 695°C or higher, 696°C or higher, 697°C or higher, 698°C or higher, 699°C or higher, and 700°C or higher, in that order. On the other hand, from the viewpoint of reducing the burden on the annealing furnace and the molding die, the glass transition temperature Tg of the above glass is preferably 750° C. or less, and more preferably 750° C. or less, 745° C. or less, 744° C. or less, 743° C. or less, 742° C. or less, 741° C. or less, 740° C. or less, 735° C. or less, 730° C. or less, and 725° C. or less in that order. The glass transition temperature Tg is determined by a differential scanning calorimeter at a heating rate of 10° C. / min.
[0046] <Method of manufacturing optical glass> The optical glass can be obtained by weighing, preparing and thoroughly mixing raw materials such as oxides, carbonates, sulfates, nitrates and hydroxides so as to obtain the desired glass composition, heating and melting the mixture in a melting vessel, degassing and stirring the mixture to produce a homogeneous, bubble-free molten glass, and then molding the glass. Specifically, the glass can be produced by using a known melting method.
[0047] [Glass material for press molding, optical element blanks, and their manufacturing methods] Another aspect of the present invention is a glass material for press molding comprising the optical glass; an optical element blank made of the optical glass; Regarding.
[0048] According to another aspect of the present invention, a method for producing a glass material for press molding, comprising a step of molding the optical glass into a glass material for press molding; a method for producing an optical element blank, comprising a step of press-molding the glass material for optical glass press molding using a press mold to produce an optical element blank; A method for producing an optical element blank, comprising the step of forming the optical glass into an optical element blank; will also be provided.
[0049] An optical element blank is an optical element base material that approximates the shape of a target optical element and has polishing margins (surface layers to be removed by polishing) and, if necessary, grinding margins (surface layers to be removed by grinding) added to the shape of the optical element. The optical element is finished by grinding and polishing the surface of the optical element blank. In one embodiment, the optical element blank can be produced by a method (called a direct press method) in which a molten glass obtained by melting an appropriate amount of the above glass is press-molded. In another embodiment, the optical element blank can also be produced by solidifying a molten glass obtained by melting an appropriate amount of the above glass.
[0050] In another embodiment, a glass material for press molding is prepared, and the prepared glass material for press molding is press molded to produce an optical element blank.
[0051] The press molding of the glass material for press molding can be carried out by a known method in which the glass material for press molding in a heated and softened state is pressed in a press mold. Both heating and press molding can be carried out in the atmosphere. By annealing after press molding to reduce distortion inside the glass, a homogeneous optical element blank can be obtained.
[0052] Glass materials for press molding include not only those called glass gobs for press molding, which are used for press molding as they are to produce optical element blanks, but also those that are mechanically processed such as by cutting, grinding, polishing, etc., and are used for press molding via glass gobs for press molding. Cutting methods include a method in which a groove is formed in the portion of the surface of the glass plate to be cut by a method called scribing, and local pressure is applied to the grooved portion from the back side of the surface on which the groove is formed, thereby breaking the glass plate at the grooved portion, and a method in which the glass plate is cut by a cutting blade. Grinding and polishing methods include barrel polishing, etc.
[0053] The glass material for press molding can be produced, for example, by casting molten glass into a mold to form a glass plate, and cutting this glass plate into a plurality of glass pieces. Alternatively, a suitable amount of molten glass can be molded to produce a glass gob for press molding. An optical element blank can also be produced by reheating, softening, and press-molding the glass gob for press molding. The method of producing an optical element blank by reheating, softening, and press-molding glass is called a reheat press method, as opposed to a direct press method.
[0054] [Optical elements and their manufacturing methods] Another aspect of the present invention is An optical element made of the above optical glass Regarding.
[0055] The optical element is produced using the optical glass. In the optical element, the glass surface may be coated with one or more layers of coating, such as a multilayer film including an anti-reflection film.
[0056] According to another aspect of the present invention, A method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank described above; will also be provided.
[0057] In the manufacturing method of the optical element, the mechanical processing such as grinding and polishing can be performed by applying a known method, and the surface of the optical element after processing can be sufficiently cleaned and dried to obtain an optical element with high internal quality and surface quality. In this way, an optical element made of the optical glass can be obtained. Examples of optical elements include various lenses such as spherical lenses, aspherical lenses, and microlenses, and prisms.
[0058] In addition, the optical element made of the optical glass is also suitable as a lens constituting a cemented optical element. Examples of cemented optical elements include a cemented lens formed by cementing lenses together, and a lens and a prism. For example, a cemented optical element can be produced by precisely processing the cemented surfaces of two optical elements to be cemented (for example, by spherical polishing) so that the shapes are inverted, applying an ultraviolet-curing adhesive used for bonding the cemented lens, bonding them together, and then irradiating ultraviolet light through the lens to cure the adhesive. In order to produce a cemented optical element in this way, the optical glass is preferable. A plurality of optical elements to be cemented are each produced using a plurality of types of glass having different Abbe numbers νd, and cemented together to produce an element suitable for correcting chromatic aberration. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.
[0060] [Example 1] <No.001~118> The raw materials for introducing each component were the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc., and the raw materials were weighed and thoroughly mixed to obtain the glass composition (unit: mol%) shown in the table below. The mixed raw materials were placed in a platinum crucible and heated in a furnace set at 1350° C. for 2 hours to melt. The molten glass was stirred to homogenize it, then poured into a preheated mold and allowed to cool to near the glass transition temperature. It was then immediately placed in an annealing furnace and held at about the glass transition temperature for about 30 minutes, after which it was slowly cooled at a rate of −30° C. / hour for 4 hours, and then allowed to cool to room temperature in the furnace to obtain the optical glasses No. 001 to 118 shown in the table below. The physical properties of the optical glass thus obtained are shown in the following table. The physical properties of the optical glasses were measured by the methods described below.
[0061] <Evaluation of physical properties of optical glass> (1) Refractive index nd Abbe number νd The refractive index nd and Abbe number vd of the obtained glass were measured by the refractive index measurement method specified by the Japan Optical Glass Industry Association.
[0062] (2) Glass transition temperature Tg The glass was thoroughly crushed in a mortar and used as a sample. A platinum cell was used as a sample container, and the glass transition temperature Tg was measured at a heating rate of 10°C / min using a Rigaku differential scanning calorimeter (DSC8271).
[0063] (3) Specific gravity Specific gravity was measured by Archimedes' method.
[0064] (4) Coloring degree λ5, λ 70 A glass sample having a thickness of 10±0.1 mm and two optically polished flat surfaces facing each other was used to measure the spectral transmittance T (%) using a spectrophotometer. The wavelength (nm) at which T is 5% is defined as λ5, and the wavelength (nm) at which T is 70% is defined as λ6. 70 It was decided.
[0065] [Table 1]
[0066]
Table 2
[0067]
Table 3
[0068]
Table 4
[0069]
Table 5
[0070]
Table 6
[0071]
Table 7
[0072]
Table 8
[0073]
Table 9
[0074]
Table 10
[0075]
Table 11
[0076]
Table 12
[0077] [Example 2] A glass gob for press molding was prepared using the various glasses obtained in Example 1. The glass gob was heated and softened in the atmosphere, and press molded in a press mold to prepare a lens blank (optical element blank). The prepared lens blank was removed from the press mold, annealed, and machined, including polishing, to prepare a spherical lens made of the various glasses prepared in Example 1.
[0078] [Example 3] A desired amount of the molten glass produced in Example 1 was press molded in a press mold to produce a lens blank (optical element blank). The produced lens blank was removed from the press mold, annealed, and subjected to mechanical processing including polishing to produce a spherical lens made of the various glasses produced in Example 1.
[0079] [Example 4] The molten glass produced in Example 1 was solidified to produce a glass lump (optical element blank), which was then annealed and machined, including polishing, to produce spherical lenses made of the various glasses produced in Example 1.
[0080] [Example 5] The spherical lenses produced in Examples 2 to 4 were bonded to spherical lenses made of other types of glass to produce cemented lenses. The cemented surfaces of the spherical lenses produced in Examples 2 to 4 were convex, and the cemented surfaces of the spherical lenses made of other types of glass were concave. The above two cemented surfaces were produced so that the absolute values of the radii of curvature were equal to each other. An ultraviolet-curing adhesive for bonding optical elements was applied to the cemented surfaces, and the two lenses were bonded together with their cemented surfaces facing each other. Thereafter, ultraviolet light was irradiated onto the adhesive applied to the cemented surfaces through the spherical lenses produced in Examples 2 to 4 to solidify the adhesive. A cemented lens was produced in the manner described above. The cemented lens had a sufficiently high bonding strength and exhibited a sufficient level of optical performance.
[0081] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. In the glass composition based on oxides expressed in mole percent, SiO 2 The content is 1.00% or more and 30.00% or less, B 2 O 3 The content is 1.00% or more and 40.00% or less, La 2 O 3 The content is 5.00% or more and 40.00% or less, G.D. 2 O 3 The content is 0.00% or more and 3.50% or less, Y 2 O 3 The content is 0.50% or more and 20.00% or less, TiO 2 The content is 5.00% or more and 30.00% or less, ZrO 2 The content is 0.00% or more and 20.00% or less, Nb 2 O 5 The content is 0.00% or more and 20.00% or less, G.D. 2 O 3 and Ta 2 O 5 The total content of 2 O 3 +Ta 2 O 5 ) is 0.00% or more and 3.50% or less, La 2 O 3 , Gd 2 O 3 and Y 2 O 3 The total content (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 ) is 26.50% or more, TiO 2 , ZrO 2 and Nb 2 O 5 The total content (TiO 2 + ZrO 2 +Nb 2 O 5 ) is 23.00% or more and 36.00% or less, Alkaline earth metal oxides RO and alkali metal oxides R 2 The total content of RO and O (RO+R 2 O) is 3.50% or more; SiO 2 Gd content 2 O 3 Molar ratio of content (Gd 2 O 3 / SiO 2 ) is 0.00 or more and 0.23 or less, SiO 2 B relative to content 2 O 3 Molar ratio of content (B 2 O 3 / SiO 2 ) is 0.80 or more and 1.56 or less, La 2 O 3 SiO content 2 Molar ratio of content (SiO 2 / La 2 O 3 ) is 0.87 or less, B 2 O 3 Y relative to content 2 O 3 Molar ratio of content (Y 2 O 3 / B 2 O 3 ) is 0.15 or more and 0.34 or less, and B 2 O 3 TiO content 2 Molar ratio of content (TiO 2 / B 2 O 3 ) is 0.70 or more and 1.10 or less, Optical glass.
2. A 2 O 3 2. The optical glass according to claim 1, wherein the content is from 0.00% to 2.00%.
3. Nb 2 O 5 2. The optical glass according to claim 1, wherein the content is 0.10% or more and 20.00% or less.
4. WO 3 2. The optical glass according to claim 1, wherein the content is from 0.00% to 0.40%.
5. La 2 O 3 , Gd 2 O 3 and Y 2 O 3 The total content (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 2. The optical glass according to claim 1, wherein the content of Cd is 26.50% or more and 35.00% or less.
6. Alkaline earth metal oxides RO and alkali metal oxides R 2 The total content of RO and O (RO+R 2 2. The optical glass according to claim 1, wherein O is 3.50% or more and 10.50% or less.
7. B 2 O 3 Y relative to content 2 O 3 Molar ratio of content (Y 2 O 3 / B 2 O 3 2. The optical glass according to claim 1, wherein σ is 0.17 or more and 0.34 or less.
8. SiO 2 B relative to content 2 O 3 Molar ratio of content (B 2 O 3 / SiO 2 2. The optical glass according to claim 1 , wherein the refractive index is 1.20 or greater and 1.56 or less.
9. La 2 O 3 SiO content 2 Molar ratio of content (SiO 2 / La 2 O 3 2. The optical glass according to claim 1, wherein σ is 0.50 or greater and 0.87 or less.
10. G.D. 2 O 3 and Ta 2 O 5 The total content of 2 O 3 +Ta 2 O 5 2. The optical glass according to claim 1, wherein the content of Cd is 0.00% or more and 2.50% or less.
11. A 2 O 3 The content is 0.00% or more and 2.00% or less, Nb 2 O 5 The content is 0.10% or more and 20.00% or less, WO 3 The content is 0.00% or more and 0.40% or less, La 2 O 3 , Gd 2 O 3 and Y 2 O 3 The total content (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 ) is 26.50% or more and 35.00% or less, Alkaline earth metal oxides RO and alkali metal oxides R 2 The total content of RO and O (RO+R 2 O) is 3.50% or more and 10.50% or less, B 2 O 3 Y relative to content 2 O 3 Molar ratio of content (Y 2 O 3 / B 2 O 3 ) is 0.17 or more and 0.34 or less, SiO 2 B relative to content 2 O 3 Molar ratio of content (B 2 O 3 / SiO 2 ) is 1.20 or more and 1.56 or less, La 2 O 3 SiO content 2 Molar ratio of content (SiO 2 / La 2 O 3 ) is equal to or greater than 0.50 and equal to or less than 0.87, G.D. 2 O 3 and Ta 2 O 5 The total content of 2 O 3 +Ta 2 O 5 2. The optical glass according to claim 1, wherein the content of Cd is 0.00% or more and 2.50% or less.
12. An optical element comprising the optical glass according to any one of claims 1 to 11.
Citation Information
Patent Citations
Optical glass and use thereof
WO2013146378A1